2019
DOI: 10.1094/pdis-06-18-1078-re
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation Method Impacts Symptom Development Associated with Diaporthe aspalathi, D. caulivora, and D. longicolla on Soybean (Glycine max)

Abstract: One hundred fifty-two Diaporthe isolates were recovered from symptomatic soybean (Glycine max) stems sampled from the U.S. states of Iowa, Indiana, Kentucky, Michigan, and South Dakota. Using morphology and DNA sequencing, isolates were identified as D. aspalathi (8.6%), D. caulivora (24.3%), and D. longicolla (67.1%). Aggressiveness of five isolates each of the three pathogens was studied on cultivars Hawkeye (D. caulivora and D. longicolla) and Bragg (D. aspalathi) using toothpick, stem-wound, mycelium conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 45 publications
3
24
0
1
Order By: Relevance
“…Comparison of mycelial plug and spore suspension assays revealed that mycelial plugs cause more severe infections than the latter. These results agree with Ghimire et al (2019) findings that the use of mycelial plugs is more effective for assessing the aggressiveness of Diaporthe spp . than using conidial suspensions.…”
Section: Discussionsupporting
confidence: 93%
“…Comparison of mycelial plug and spore suspension assays revealed that mycelial plugs cause more severe infections than the latter. These results agree with Ghimire et al (2019) findings that the use of mycelial plugs is more effective for assessing the aggressiveness of Diaporthe spp . than using conidial suspensions.…”
Section: Discussionsupporting
confidence: 93%
“…The high proportion of D. longicolla isolates associated to canker lesions was surprising, although we confirmed by inoculation assays that D. longicolla produces similar stem lesions as those caused by D. caulivora. This is consistent with recent results obtained by Ghimire et al (2019). D. longicolla has been previously isolated from SSC lesions (Gebreil et al, 2015;Mathew et al, 2015); it has been associated to black zone lines on the lower stems of soybean plants (Olson et al, 2015), and it causes soybean stem blight (Cui et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…These authors found a significant interaction between inoculation methods and isolates, confirming that the inoculation method influenced the disease caused by D. helianthi, and pointed out that although inoculation by mycelial plugs has many advantages, such as the efficiency to detect significant differences in the severity of the disease, and the efficient use of space and the time required to inoculate the plants, it does not replicate the natural infection process by Diaporthe spp. Ghimire et al (2019), stated that inoculation methods have a significant impact on the development of symptoms caused by some Diaporthe species on soybean, indicating that wound-based inoculation methods resulted in the greatest disease severity ratings.…”
Section: Discussionmentioning
confidence: 99%